Tunggu Tubang Sebagai Mekanisme Hukum Adat Pewarisan Pada Masyarakat Semende - Bunga Dwi Malika; Halifa Suci Puspita; Rahel Stanford (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Tunggu tubang is a customary inheritance system that continues to exist within the Semende community of South Sumatra. This system appoints the eldest daughter as the custodian and manager of family ancestral property, including houses and agricultural land, for the collective benefit of the extended family. This research aims to analyze the position of tunggu tubang as a customary law inheritance mechanism and to examine its role in maintaining family sustainability and social order within the indigenous community. The study employs normative legal research with a juridical-normative approach using literature review and qualitative descriptive analysis. The findings indicate that tunggu tubang does not grant absolute ownership to women but assigns them the responsibility to manage ancestral property based on communal values, social responsibility, and sustainability principles. The system contributes to food security and food sovereignty through the intergenerational management of agricultural land. From a gender perspective, tunggu tubang reflects recognition of women’s strategic roles, although it also entails significant social responsibilities. Furthermore, this practice can coexist with Islamic law and national law as long as it does not contradict fundamental legal principles. Therefore, tunggu tubang represents a form of harmonization between customary law, religious law, and national law within the Semende community.